DIFFERENTIATION OF THE WHITE AND PURPLE FLOWER FORMS OF Orthosiphon aristatus (Blume) Miq. BY 1D and 2D CORRELATION IR SPECTROSCOPY (Jurnal Teknologi (Sciences & Engineering), 2015)
Orthosiphon aristatus (Blume) Mig. is also known as Misai kucing or Kumis kucing. The plant is traditionally used to treat tonsilities, fever, menstrual disorders, gonorrhea, syphilis, gallstones, rheumatism, diabetes, hypertension, epilepsy, edema, hepatitis jaundice and for diuretic activity. The objective of this work was to differentiate the white and purple flower forms of O. aristatus (Blume) by multi-steps infrared (IR) macro-fingerprinting. The analyses included Fourier transform infrared spectroscopy (FT-IR), second derivative IR spectroscopy and two-dimensional correlation infrared (2D IR) spectroscopy with thermal perturbation. A distinctive absorption peak at 1384 cm-1 from the purple flower form clearly differentiated the two forms of O. aristatus. Further differentiation was made by the appearance of a strong auto-peak at 1580 cm-1 for the white flower form and at 1546 cm-1 for the purple flower form. Such results indicate that the multi-steps infrared macro-fingerprinting has the potential for the development of a fast and reliable analytical methodology for distinguishing the white and purple flower forms of O. aristatus (Blume) Miq. effectively.